Keanekaragaman Jenis Gastropoda di Pantai Kadahang Kabupaten Sumba Timur - Erli Dai Waha; Anita Tamu Ina (Bioscientist : Jurnal Ilmiah Biologi, 2023)
The purpose of this study was to determine the diversity of gastropod species in Kadahang Beach, East Sumba Regency. This type of research is a quantitative descriptive using the Shannon-Wiener diversity index formula. Sampling using purposive sampling technique. Gastropod samples were counted using the quadratic transect technique with a size of 1 x 1 meter placed perpendicular to the inside of 50 meters using a plot of 30 plots. The environmental factors measured were temperature, salinity, and degree of acidity (pH). Measurements were made at two observation stations. The results showed that 10 species of gastropods were divided into 7 families, 10 genera and 5 orders, namely the orders Littorinimorpha, Archaeogastropoda, Neogastropoda, Trochida, and Cycloneritida with a total of 235 individuals. The types of gastropods found were Conomurex luhuanus, Lambis lambis, Gibberulus gibbosus, Canarium labiatum, Turbo chrysostomus, Cymbiola vespertifilio, Vasum turbinelus, Trochus maculatus, Blasicrura pallidula, and Nerita signata. The diversity index obtained is in the moderate category with a value of H' = 2.168.